(untitled) (Experimental biology, 2017)
Introduction of and introduction to the culture of new, more productive forms and types of forage plants is now a very topical issue. This is especially important for Kazakhstan, where the livestock industry is one of the leading sectors of the economy where, in addition to other tasks carried out intensive searches for new fodder crops with a high yield and high in carbohydrates in the diet. In this regard, the interest is tropical grasses, have a number of agronomic traits: high productivity, responsiveness to fertilizer and irrigation, mnogoukosnostyu, long-term cycle of vegetation, drought-and heat-resistant, resistant to grazing. The aim of our study was to identify factors influencing the growth and development of unfertilized ovaries Brachiaria under aseptic conditions. The results of these studies have revealed the dependence of the regeneration processes in the culture of unfertilized ovaries of Brachiaria genotypes of the initial plant, mineral and hormonal composition of culture medium.